2014
DOI: 10.4269/ajtmh.14-0102
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological Study of Outdoor Recreationists' Exposure to Spotted Fever Group Rickettsia in Western Australia

Abstract: Abstract. Bushland activity has previously been linked to rickettsial exposure in eastern and central regions of Australia, whereas little is known about the risks in Western Australia. The isolation of Rickettsia gravesii sp. nov. from Amblyomma triguttatum ticks and anecdotal reports of low-grade illness among bush recreationists raised the possibility of rickettsial transmission in the State. This study investigated rickettsial seroprevalence and potential risk of exposure to the spotted fever group rickett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…Rickettsial disease has historically been associated with higher rates in men and those of older age; however, recent studies on risk of rickettsial exposure demonstrated that there are no significant differences between gender or age groups (24,25). Other factors that have been found to influence rickettsial disease severity include underlying patient disease and enhanced oxidative stress (26).…”
Section: Virulence Pathogenesis and Clinical Presentationmentioning
confidence: 99%
“…Rickettsial disease has historically been associated with higher rates in men and those of older age; however, recent studies on risk of rickettsial exposure demonstrated that there are no significant differences between gender or age groups (24,25). Other factors that have been found to influence rickettsial disease severity include underlying patient disease and enhanced oxidative stress (26).…”
Section: Virulence Pathogenesis and Clinical Presentationmentioning
confidence: 99%
“…In Australia, Flinders Island spotted fever is an Australian tick borne disease caused by R. honei (also known as strain TT-118). It was first discovered on Flinders Island, Tasmania, but has since been detected in clinical patients from other parts of Australia, including in South Australia [ 5 , 6 ]. There has also been a reported cases of Flinders Island spotted fever in Nepal [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coastal Eastern Australia-Northern QLD south to Flinders Island, Tasmania, 1946-1989(Sexton et al, 1991 2006(Abdad et al, 2014 23% (n = 61) of recreational rogainers were seropositive for spotted fever group Rickettsia in 2.7% (n = 47) of controls (Perth residents, no occupational or recreational bias) were seropositive for spotted fever group rickettsiae. 26/920 (2.8%) seropositive for potted ever group Exposure: Outdoor recreational activities were significant risk factors Barrow Island & Perth area, Western Australia.…”
Section: Spotted Fever Group Rickettsioses In Oceaniamentioning
confidence: 98%